2015
DOI: 10.3917/redp.246.0953
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Consolidation, Public Debt and Output Dynamics in the Euro Area: lessons from a simple model with time-varying fiscal multipliers

Abstract: EMU countries have engaged in a consolidation of fiscal policies since 2011. This paper deals with the public debt and output dynamic consequences of this strategy. To this end, we develop a simple macroeconomic model of the Euro area, where fiscal multiplier is time-varying. Recent empirical evidence has indeed shown that fiscal multipliers were higher in time of crisis. We then analyze the ability of EMU countries to comply with the new fiscal rules on public debt. The path of public debt and output gap is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Researching on fiscal consolidation, public debt and output dynamics in the Euro area and using time varying fiscal multipliers model, [29] suggested that not all European Monetary Union countries would likely reach debt to GDP ratio of 60 percent and above by 2032. Because output gap was nearly closed in Germany and therefore it would not be prudent for them to implement expansionary fiscal policy as this will lead to a low spillover effects which will not be Theoretical Economics Letters significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researching on fiscal consolidation, public debt and output dynamics in the Euro area and using time varying fiscal multipliers model, [29] suggested that not all European Monetary Union countries would likely reach debt to GDP ratio of 60 percent and above by 2032. Because output gap was nearly closed in Germany and therefore it would not be prudent for them to implement expansionary fiscal policy as this will lead to a low spillover effects which will not be Theoretical Economics Letters significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The consolidation processes extensively hinge on the fiscal multipliers (i.e. a measure of the short-term impact of discretionary fiscal policy on output), which were sizeable during the sovereign debt crisis (Blot, Cochard, Creel, Ducoudré et al 2014;Batini, Eyraud, Forni and Weber 2014). By accounting poorly for multipliers' effects, and due to the synchronised consolidation cycle of the MS, the position of the fiscal indicators deteriorates.…”
Section: Source: Author's Creationmentioning
confidence: 99%
“…Reasons for this performance vary and may be explained through the (de)synchronisation of business cycle cycles, 8 which occurred repeatedly during the sampled period. As the synchronisation appears to be stronger among the countries sharing the same currency (De Grauwe and Ji 2017), the negative spillovers on growth thus get amplified (Blot et al 2014), making the countries unable to reduce the negative excesses. Another possible cause is the constant rise of debt levels in the MS in past years and therefore a persistent breach of the SGP benchmark that has not been adequately monitored (for example the arguably ineffective EDP or the absence of the European semester prior to the 'Six-Pack').…”
Section: Source: Author's Creationmentioning
confidence: 99%
“…Au cours de la décennie d'avant-crise, l'Allemagne s'est lancée dans une stratégie de désinflation compétitive 2. Pour une revue de la littérature sur la valeur des multiplicateurs, voir Creel, Heyer et Plane (2011), Heyer (2012 ou Blot et al (2014). qui lui a permis de gagner sur l'ensemble des pays de la zone euro en termes de « compétitivité coût du travail ». Les CSU français ont eu une évolution très proche de celle de la moyenne des pays partenaires de la zone euro.…”
Section: Des éVolutions Du Chômage Fortement Corrélées à La Croissancunclassified